Education as the First Guard in Practicing Religious Tolerance in Tambakrejo Village - Moh. Zubaidi Abdul Ghofur; Hana Berliana Mualimah; Siti Rizki Nurhidayah; Miftachul Anam; Merly Serla Marlela; Nikmatul Ulumia; Atiqoh Al-Amin; Muhammad Abdul Rosyid Albana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Education about religious tolerance is very important to instill. A sense of tolerance in students can be instilled and can be improved through education, especially in character education. Since children have been in elementary school, it is time for them to understand what tolerance is so that later children do not do things that should not be done to people who think they are different from themselves. In-depth education about tolerance can help prevent prejudice, discrimination and conflict in society. Therefore, there needs to be a serious effort to integrate tolerance lessons into the elementary school curriculum in order to create a generation that is more tolerant and open to differences.